2005
DOI: 10.1021/bi0477081
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Modeling of Human Lysozyme Reveals a Unique Nonapeptide, HL9, with Anti-HIV Activity

Abstract: We previously reported that lysozyme accounts for anti-HIV activity associated with the beta-core fraction of human chorionic gonadotropin [Lee-Huang, S., Huang, P. L., Sun, Y., Kung, H. F., Blithe, D. L. & Chen, H. C. (1999) Proc Natl Acad Sci U S A 96, 2678-81]. To define the structural and sequence requirements for anti-HIV activity, we carried out peptide fragmentation and activity mapping of human lysozyme. We identified two peptides that consist of 18 and 9 amino acids of human lysozyme (HL18 and HL9), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 26 publications
(30 reference statements)
0
78
0
1
Order By: Relevance
“…30 Gene expression analysis for innate immune molecules with anti-HIV potential such as SLPI, 5,36 ␤-defensins, 7 and thrombospondin 4 showed a trend for decreased expression in the tonsil epithelium. Of the molecules examined, only lysozyme, a broad-range antimicrobial factor with limited evidence of direct HIV targeting 37 was significantly up-regulated in the tonsil. SLPI, a protein with demonstrated anti-HIV activity in vivo and in vitro 46 was minimally expressed in the tonsil while abundant in the oral epithelia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Gene expression analysis for innate immune molecules with anti-HIV potential such as SLPI, 5,36 ␤-defensins, 7 and thrombospondin 4 showed a trend for decreased expression in the tonsil epithelium. Of the molecules examined, only lysozyme, a broad-range antimicrobial factor with limited evidence of direct HIV targeting 37 was significantly up-regulated in the tonsil. SLPI, a protein with demonstrated anti-HIV activity in vivo and in vitro 46 was minimally expressed in the tonsil while abundant in the oral epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…4 Interestingly, SLPI, defensins, and thrombospondin were expressed at a lower level in the tonsil epithelium (1.5-to 3-fold), although only SLPI was significantly different between tonsil and gingiva (P Ͻ 0.05). By comparison, lysozyme, a broad-range anti-viral factor with limited evidence of direct HIV activity, 37 was highly expressed in the tonsil (P Ͻ 0.05, Figure 5A). Immunohistochemical studies for SLPI revealed a striking difference of expression between tissues ( Figure 5B).…”
Section: Increased Production Of Slpi In the Oral Epitheliamentioning
confidence: 99%
“…The addition of lysozyme to baby formulas was proposed (4), and lysozyme had also been shown to inhibit the growth of HIV-1 in vitro. Of note, the anti-HIV activity of lysozyme is independent of its muramidase activity (5). In addition, findings of previous studies have shown that it is effective in inactivating spores of Bacillus cereus in cheese by causing high hydrostatic pressure following the addition of lysozyme (6).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the well-known muramidase activity of HL, increasing evidence suggests the existence of non-enzymatic and/or nonlytic modes of action against Gram-negative and Gram-positive bacteria (Lee-Huang et al 2005;Masschalck & Michiels, 2003). Furthermore, lysozyme has antitumor (Osserman et al 1973) and antiviral activities (Lee-Huang et al 2005), and it enhances the immune system (Siwicki et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, lysozyme has antitumor (Osserman et al 1973) and antiviral activities (Lee-Huang et al 2005), and it enhances the immune system (Siwicki et al 1998). The mechanisms of these activities remain unclear, and the dominant questions involve how HL recognizes pathogenic microbes.…”
Section: Introductionmentioning
confidence: 99%